Xanthogranulomatous pyelonephritis presenting as a left‐sided pleural effusion. Issue 9 (21st October 2018) - Huang, Maple; Sum, Reuben; Deshpande, Sheetal; Joosten, Simon A.
Abstract : Xanthogranulomatous pyelonephritis (XGP) is a rare chronic granulomatous process that affects the kidneys. It is usually associated with longstanding urinary tract infections and obstruction. Patients suffering from XGP typically present with undifferentiated symptoms, including abdominal pain, weight loss, and intermittent fevers. For this reason, diagnosis is often delayed until patients are acutely unwell with sepsis. Abstract : We present the case of a 42‐year‐old male who presented to the emergency department with a left‐sided pleural effusion on plain radiograph and computed tomography. Further imaging of the abdomen indicated that this effusion was secondary to a splenic hilar abscess complicating a left‐sided xanthogranulatous pyelonephritis.